The Correlation Between Student Discipline and Parental Attention on Junior High School Students’ Science Learning Outcomes - Desi Fitriani; Dios Sarkity; Nevrita Nevrita (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
This study aims to examine the relationships between learning discipline and parental attention and science learning outcomes among Grade VIII students at a public junior secondary school in Tanjungpinang. A quantitative approach with a correlational research design was employed. All Grade VIII students (N = 130) were involved as research participants using a total sampling technique. Data on learning discipline and parental attention were collected through closed-ended questionnaires, while students’ science learning outcomes were obtained from documentation of end-of-semester summative assessment scores. The data were analyzed using descriptive statistics, Pearson product–moment correlation, and multiple correlation analysis. The results reveal that learning discipline is positively and significantly associated with science learning outcomes, as is parental attention. Moreover, learning discipline and parental attention jointly demonstrate a significant positive relationship with students’ science learning outcomes. These findings suggest that students’ academic achievement in science is influenced by the combined contribution of internal factors related to students’ learning behaviors and external support originating from the family environment